PROJECT-BASED LEARNING DURING ONLINE EDUCATION: CASE OF THE MASTER PROGRAM ON BUSINESS MANAGEMENT IN THE DIGITAL ECONOMY - Tsenzharik, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the article, we will share the experience of implementing PBL at the Master program on Business Management in the Digital Economy held in Saint Petersburg University. Specific conditions for the PBL organization are highlighted. First, digital transformation process is quite difficult to realize in companies, as no clear methodology for its implementation exist yet. Second, pandemic left the only opportunity for online communication, and all usual administration and education processes had to be changed. The experience is structured and presented with recommendations for similar projects.